Optimizing the workforce for an assembly line: Human-centric approach towards Industry 5.0 - Andersén, Johan (My University, 2022)
When a company aims to improve their technological solutions for their processes with the most recent ones, studies show that it will help the companies gain several benefits. The newest technological trend (Industry 5.0) has a more human-centric approach. The trend is to bring back the human workers to work alongside the machines and not automate every process. This trend shows that the focus should be more on the human workforce and optimizing the workforce by eliminating and improving bottlenecks. This thesis study aims to find a suitable technological solution for the case company, how to optimize the workforce for their assembly line workers at their new factory. In order to optimize the workforce, the assembly line employees' tasks need to be analyzed and evaluated so that they are more fluid and efficient. Furthermore, the assembly line needs to be freed of bottlenecks (situations where production is hindered). Some possible technologies for the final solution of this thesis case subject are presented, and the final optimal solution will be presented in more detail in the results chapter. Also, which areas to focus on and improve are explained and how to optimize a workforce. A thorough research process methodology (Design Science Research (DSR)) is used to find the most optimal solution. The DSR process is explained in detail and how it is utilized for this research process about the thesis subject. The key elements to focus on when a company wants to optimize their workforce are: task management, communication, quality management, and the workers' well-being. The DSR research process showed that it is possible to utilize task management and communication to optimize the workforce with today's technology. Utilizing wearable hardware (a smartwatch) with software (Aucobo) to optimize the workforce was an ideal solution for this case. The software and hardware will be presented in detail. A use case scenario and how to program the task with the software are also presented.
Keywords: smartwatches; optimisation; industry; corporate strategies; employees; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management